Improving Academic Performance in Geometry Using a Mastery Learning Approach through GeoGebra - Paweena Khansila,; Wannatida Yonwilad,; Prapaporn Nongharnpituk,; Suwannawat Thienyutthakul, (Journal of Educational Issues, 2024)
The objectives of these quasi-experimental methods were to improve academic performance in geometry using a mastery learning approach through GeoGebra for mathematics teacher students and to investigate students’ satisfaction with using a mastery learning approach through GeoGebra in geometry. The participants were divided into two groups, involving 30 and 29 students, respectively. The experimental group with 30 students received instruction in the mastery learning approach through GeoGebra, while the control group received a traditional education in learning geometry. At the end of the lessons, post-tests were administered to both groups. The statistical difference between the participant’s post-test academic performance in the experimental and control groups was analyzed with an independent sample t-test after examining the assumptions of this test, namely normality and homogeneity in each group, while percentages and means were used to assess the satisfaction of the experimental group. The instruments used were the Geometry Achievement Test (GAT), which consists of 2D and 3D dimensions, and a questionnaire with satisfied students. Results of the study indicated that the scores of academic performances in the experimental group were significantly higher than those of the control group. Analysis of the questionnaire responses indicated a positive overall satisfaction with using a mastery learning approach through GeoGebra in geometry. On the other hand, instruction with a mastery learning approach through GeoGebra supported students’ learning of these subjects meaningfully and conceptually.